Detection of multiple sclerosis using blood and brain cells transcript profiles: Insights from comprehensive bioinformatics approach. (2019) - Islam, Tania; Rahman, Md. Rezanur; Karim, Md. Rezaul; Huq, Fazlul; Quinn, Julian M.W.; Moni, Mohammad Ali
Abstract: Multiple sclerosis (MS) is a severely disabling disease affecting the brain and spinal cord. The detection of MS at an early stage is difficult. However, detection of MS from blood cell gene expression may ameliorate the early identification of MS. The present study addressed overlapped genes between blood cell and brain tissues of MS patients. We analyzed microarray gene expression brain tissue datasets and eQTL data to identify overlapped genes in the blood and brain of MS patients. We identified 23 overlapped differentially expressed genes (DEGs) (PWP2, UPK3BL, NFATC3, NPIPA5, KNOP1, PIK3C2B, LDLRAP1, HN1L, FAM226B, STAG3L2, ZNF814, BMS1P5, SDCCAG8, CLN8, ARHGEF7, NEAT1, ANKRD42, C5orf34, DOK6, PKN2, SP1, DBF4B, VAMP3) in the blood cells and brain tissues of MS patients. The axon guidance mediated and postsynaptic differentiation associated pathways were enriched by the DEGs. The significant regulatory transcription factors (TFs) including SP1, ARNT, MEF2A, YY1, EGR1, MIF, FOS, NFYA, TFAP2A, MYC, USF, MXI1, JUN, MAX, E2F1, POU3F2, GABPA, TFAP2C, CUX1, 2623, SPI1 and microRNAs (miRNAs) including miR-650, miR-223, miR-9, miR-181b, miR-190, miR-561, miR-520c-3p, miR-658, miR-199b-5p, miR-660, miR-20 were identified in MS. The candidate drugs were determined from drug target overrepresentation analysis. This study provides biomarkers at protein levels (hub proteins and TFs) and RNA levels (mRNAs, miRNAs) in MS subjects that were similarly dysregulated in both blood and brain tissues.